Proteome-Wide Analysis of Heat-Stress in Pinus radiata Somatic Embryos Reveals a Combined Response of Sugar Metabolism and Translational Regulation Mechanisms - Castander-Olarieta, Ander (2021)
Somatic embryogenesis is the process by which bipolar structures with no vascular connection with the surrounding tissue are formed from a single or a group of vegetative cells, and in conifers it can be divided into five different steps: initiation, proliferation, maturation, germination and acclimatization. Somatic embryogenesis has long been used as a model to study the mechanisms regulating stress response in plants, and recent research carried out in our laboratory has demonstrated that high temperatures during initial stages of conifer somatic embryogenesis modify subsequent phases of the process, as well as the behavior of the resulting plants ex vitro. The development of high-throughput techniques has facilitated the study of the molecular response of plants to numerous stress factors. Proteomics offers a reliable image of the cell status and is known to be extremely susceptible to environmental changes. In this study, the proteome of radiata pine somatic embryos was analyzed by LC-MS after the application of high temperatures during initiation of embryonal masses [(23°C, control; 40°C (4 h); 60°C (5 min)]. At the same time, the content of specific soluble sugars and sugar alcohols was analyzed by HPLC. Results confirmed a significant decrease in the initiation rate of embryonal masses under 40°C treatments (from 44 to 30.5%) and an increasing tendency in the production of somatic embryos (from 121.87 to 170.83 somatic embryos per gram of embryogenic tissue). Besides, heat provoked a long-term readjustment of the protein synthesis machinery: a great number of structural constituents of ribosomes were increased under high temperatures, together with the down-regulation of the enzyme methionine-tRNA ligase. Heat led to higher contents of heat shock proteins and chaperones, transmembrane transport proteins, proteins related with post-transcriptional regulation (ARGONAUTE 1D) and enzymes involved in the synthesis of fatty acids, specific compatible sugars (myo-inositol) and cell-wall carbohydrates. On the other hand, the protein adenosylhomocysteinase and enzymes linked with the glycolytic pathway, nitrogen assimilation and oxidative stress response were found at lower levels.